Migration and Climate Change Analysis: Towards Causal Factor Understanding in the Mesoamerican Dry Corridor - Vallejos Mihotek, Mara Luana; Rejas Ayuga, Juan Gregorio (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2022)
The main research objective is to advance in the understanding of the causes that imply the migratory processes produced in the last decades in the Mesoamerican Dry Corridor. A closely related variable is analysed, such as land cover and land use change, exacerbated by the effects of climate change in this region, one of the most vulnerable on Earth according to the Intergovernmental Panel on Climate Change (IPCC) of 2019 last report. Spatial data from the European Copernicus Program and historical records from NASA, and the relationship between the population estimate according to the GPWv4 and WorldPop models and the changes in vegetation based on MODIS data for 2015 and 2020 have been analyzed. The first results are discussed, and conclusions are presented in accordance with international research.